Anticipation of nitrogen fertilization and their implications on nutrient concentrations and maize yield - Nascimento, Flávia M; Bicudo, Silvio José [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Rodrigues, J G L; Fernandes, Jairo C. (GN1 Sistemas e Publicacoes, 2013)
The objective of this study is to evaluate the response of maize crop in succession to winter crops, with the anticipation of nitrogen applications on the black oat crop, in increasing doses, in no–tillage system. The experiment was conducted at the FCA/UNESP, Botucatu campus. The experimental design used was randomized blocks with four replications, in a scheme of subdivided plots. The parcels of 0, 20, 40 e 60 kg ha-1 of nitrogen doses were applied on the black oat crop and the doses applied to the maize crop were considered subparcels, varying in the following doses: 60, 80, 100 and 120 kg ha-1, applied in two parcel in the maize crop. The foliar diagnosis was carried, by occasion, at the flourish and after harvest the productivity was calculated. The results indicate that the effect of the anticipated application of N in maize is dependent on the former crop, and that the doses and time of those applications had influenced in the concentrations of the nutrients, reflecting in the productivity of the maize crop.

El objetivo de la investigación fue evaluar la respuesta del maíz en la sucesión de los cultivos de invierno, con la anticipación de la aplicación de nitrógeno en el cultivo de avena, en dosis crecientes, en sistema de siembra directa - SPD. El experimento se realizó en la FCA/UNESP, campus de Botucatu-SP. El diseño experimental fue de bloques al azar con cuatro repeticiones, en parcelas divididas, las parcelas se consistieran del nitrógeno aportado en la avena: 0, 20, 40 y 60 kg ha-1 de nitrógeno y las dosis aportadas en cobertura en cultivo del maíz, consistieron en las parcelas secundarias, con las siguientes dosis: 60, 80, 100 y 120 kg ha-1, aportado de forma dividida en cuotas en dos etapas de desarrollo del maíz. El análisis de las hojas fue tomada durante la floración y después de la cosecha se calculó el rendimiento total. Los resultados indican que el aporte anticipado de N en el maíz depende del cultivo anterior y que las tasas y las épocas de estas aplicaciones influyeron en las concentraciones de nutrientes, lo que influencia en la productividad del maíz.

O objetivo da pesquisa foi avaliar a resposta da cultura do milho em sucessão à culturas de inverno, havendo a antecipação da aplicação do nitrogênio na cultura da aveia, em doses crescentes, no SPD. O experimento foi conduzido na FCA/UNESP, Campus de Botucatu-SP. O delineamento experimental foi de blocos ao acesso com quatro repetições, em parcelas subdivididas, sendo consideradas parcelas as doses de nitrogênio aplicadas na cultura da aveia: 0, 20, 40 e 60 Kg ha¹ e as doses de nitrogênio aplicadas em cobertura na cultura do milho, foram consideradas subparcelas, variando as seguintes doses: 60, 80, 100, 120 kg ha¹, aplicados de forma parcelada em dois estádios da cultura do milho. A diagnose foliar foi feita por ocasião do florescimento e após a colheita foi calculada a produtividade. Os resultados indicam que a aplicação antecipada de N na cultura do milho é dependente da cultura antecessora e que as doses e épocas destas aplicações influíram nas concentrações dos nutrientes, refletindo na produtividade do milho.
Anticipación del aporte del abono nitrogenado y sus implicaciones en concentración de nutrientes y productividad del maíz
Antecipação da adubação nitrogenada e suas implicações na concentração de nutrientes e produtividade do milho
Keywords: Fertilizer; Management of fertilizer; Mineral nutrition; Fertilizantes; El manejo del abono; Nutrición mineral; Fertilizantes; Manejo de adubação; Nutrição mineral